Small form factor PCs - Weaver, Matthew; Wessels, Duane; Safari eBooks (Sebastopol, Calif. : O'Reilly Media, 2008)
This book demonstrates how to build small form factor PCs from kits and from scratch. It includes step-by-step instructions for building eight different systems and projects for building digital audio jukeboxes, digital video recorders, wi-fi extenders, and more.
Title from title screen.
"Build a computer that fits inside anything"--Cover.
Includes index.
Electronic reproduction.
Keywords: Microcomputers -- Design and construction; Microcomputers -- Upgrading; Electronic books